Comparative antidepressant effects and safety of intravenous racemic ketamine, psilocybin and theta burst stimulation for major depressive disorder: A systematic review and network meta‐analyses of randomized controlled trials - Itsuki Terao; Wakako Kodama (PCN Reports)
Abstract The individual efficacy and safety of intravenous racemic (IV) ketamine, psilocybin, and theta burst stimulation (TBS) for major depressive disorder have been demonstrated through meta‐analyses of randomized controlled trials (RCTs), but the comparative usefulness of these novel treatments has not yet been fully examined. We systematically searched the CENTRAL, Medline, CINHAL, and ClinicalTrials.gov databases for randomized controlled trials up to July 4, 2024. Random‐effects network meta‐analyses were conducted to compare the Comparative antidepressant effects and safety of intravenous racemic ketamine, psilocybin and theta burst stimulation for major depressive disorderantidepressant efficacy, tolerability, and acceptability of IV ketamine, psilocybin, and TBS. Twenty‐eight RCTs were included. All treatments were superior to placebo, with IV ketamine and psilocybin showing significantly greater antidepressant efficacy than TBS. No significant differences were detected between all treatments and placebo in tolerability and acceptability. In a subgroup analysis focusing on short periods of 1 week or less, only IV ketamine was significantly more effective than placebo. In another subgroup analysis focusing on periods of 4 weeks or longer, IV ketamine and psilocybin showed significantly better antidepressant effects than placebo. The confidence in the evidence ranged from very low to moderate. Specifically, there is a scarcity of studies on psilocybin and a lack of direct comparison trials. The findings suggest that IV ketamine and psilocybin may be more effective treatments compared to TBS. Additionally, IV ketamine may have an advantage in terms of rapid onset of action. The number of included studies is limited, especially for psilocybin, and therefore the current findings are preliminary, necessitating further accumulation of direct‐comparison RCTs.